Electrical protection relays Sec. 1.5 Vibration, shock, bump and seisemic testing Subsec 1.5.2 Specification for shock and bump tests (BSI, 1989)
Relays, Switches, Switchgear, Protective relays, Electrical protection equipment, Mechanical testing, Vibration testing, Environmental testing, Earthquake-resistant design